The Effect of Using English Songs by Olivia Dean through Spotify on Students’ Vocabulary Mastery at Vocation High School - Raifhannisa Adiibah Alvan; Ade Ismail Ramadhan Hamid; Abdul Halim (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2026)
This study aims to investigate the effect of using English songs by Olivia Dean through Spotify on students’ vocabulary mastery at SMK Negeri 1 Tenggarong. Vocabulary mastery is an essential component for supporting both academic achievement and workplace communication in vocational contexts, yet conventional instruction often lacks engagement. This study employed a quantitative one-group pre-experimental pretest–posttest design involving 34 eleventh-grade students from the Accounting and Financial Institution program selected through purposive sampling. The instrument was a fill-gap lyric vocabulary test based on the song “So Easy (To Fall In Love).” Data were collected through a pretest, four treatment sessions, and a posttest, and analyzed using descriptive statistics and the Wilcoxon Signed Rank Test. The results show a significant improvement in students’ vocabulary mastery, with mean scores increasing from 57.06 in the pretest to 92.35 in the posttest (Z = -5.125, p < 0.05, r = 0.879). The effect size indicates a very strong impact. These findings demonstrate a significant pedagogical impact of integrating structured song-based instruction through digital platforms. In practice, vocational EFL teachers can incorporate lyric-based listening activities and repeated exposure through streaming platforms to support effective and engaging vocabulary learning.